Analisis Sistem Akuntansi Penggajian Pegawai Dinas Lingkungan Hidup - Wahyuni Wahyuni (Pusat Riset dan Inovasi Nasional, 2024)
To find out how the employee payroll accounting system at the District Environmental Service is. Mandailing Christmas. using qualitative descriptive methods. Data collection techniques use observation, interviews and documentation studies. The results of the research show that: a) The sections or functions related to handling the payroll system include the personnel section, payroll maker section, finance section, cash sub-section, bookkeeping section, budget sub-section, and recording journal section. b) The documents used include: : Constant data (employee name attendance list, taxpayer identification number (NPWP), marital status and number of dependents, amount of non-taxable income, salary amount, division of work, BPJS contributions) and variable data (number of hours or days worked, number leave, leave, or illness, holidays, and cumulative income and tax deductions). c) The accounting records used are the accounting records used at the District Environmental Service. Mandailing for each OPD only uses manual recording which is then reported to BPKPAD to be entered into the payroll system. d) The network of procedures that form the payroll system, namely in its implementation the procedures for recording employee attendance and the documents used, as well as the procedures for paying salaries to employees are implemented into one series of activities.